PENGARUH CORPORATE SOCIAL RESPONSIBILITY, INTENSITAS ASET TETAP, DAN PROFITABILITAS TERHADAP TAX AVOIDANCE DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN SEKTOR ENERGI DI BURSA EFEK INDONESIA PERIODE 2020–2025 - Gunawan, Oka; Indriyanto, Erwin (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR), fixed asset intensity, and profitability on tax avoidance, with firm size serving as a moderating variable in energy sector companies listed on the Indonesia Stock Exchange during the 2020–2025 period. The study employs a quantitative approach with an associative design and uses secondary data derived from financial statements and annual reports. The sample was determined through purposive sampling, resulting in 30 companies with a total of 180 observations. Data were analyzed using panel data regression with the assistance of EViews through descriptive statistical analysis, classical assumption testing, panel model selection, simultaneous testing, partial testing, and coefficient of determination analysis. The model selection results indicate that the Fixed Effect Model (FEM) is the most appropriate model. Partially, CSR has a significant negative effect on tax avoidance, while fixed asset intensity and profitability have significant positive effects on tax avoidance. Firm size is proven to moderate the relationship between CSR, fixed asset intensity, and profitability and tax avoidance. Simultaneously, all independent variables and their interactions have a significant effect on tax avoidance. The R-squared value of 0.812 indicates that 81.2% of the variation in tax avoidance can be explained by the research model. These findings confirm that tax avoidance behavior in energy sector companies is influenced not only by the firms’ internal characteristics, but also by firm size, which strengthens the direction of the relationships among variables. This study provides empirical contributions to the development of corporate taxation literature and may serve as a reference for regulators in strengthening oversight in the energy sector.